Foreign Direct Investment Influences the Development of Stock Market (Journal of Asian Development Studies, 2022)
The objective of this investigation also includes the determination of impact of these two main factors whether related or not in Pakistan owing to reason that it varies country to country. The important benefit lies on the substitution or complementary part of FDI in the stock market development. A few other significant factors domestic savings, GDP growth and exchange rate have been also collaborated into this investigation together with our important independent supportive factor FDI. A positive important influence of FDI is found on the growth of stock market by use of time series data in duration from 1990 to 2021 under ordinary least squares (OLS). It is found that nearly 73% rise in the growth of Stock market with a 1% rise in FDI. While exploring other variables, domestic savings, exchange rate can have a positive and negative significant effect respectively; GDP development has an important influence on the growth of stock market but Inflation has negative and insignificant impact. This behaviour is the validation of our expectations.